A concise clinician's guide to therapy for hidradenitis suppurativa - Emily Nesbitt, BA; Stephanie Clements, MD; Marcia Driscoll, MD, PharmD (Wolters Kluwer, 2020)
Hidradenitis suppurativa (HS) is a chronic, often debilitating, skin condition that historically does not respond well to treatment. Although there is no cure for HS, symptoms can be managed if the appropriate diagnosis is made. HS most commonly develops in postpubertal women and manifests as painful, deep-seated, inflamed lesions, including nodules, sinus tracts, and abscesses. HS flares are marked by increased pain and suppuration at varying intervals and can occur in women before menstruation. HS is commonly misdiagnosed; physicians might mistake a lesion for an infection, abscess, or sexually transmitted infection. Incision and drainage of these lesions often leads to recurrence. Given that management of this chronic disease is often difficult, we sought to outline current diagnosis and management strategies for HS. Keywords: Hidradenitis suppurativa, Treatment in women and pregnancy